The effect of prolonged dietary sodium nitrate treatment on the hypothalamus-pituitary-gonadal axis and testicular structure and function in streptozotocin-induced diabetic male rats. Issue 3 (4th March 2020) - Oghbaei, Hajar; Hamidian, Gholamreza; Alipour, Mohammad Reza; Alipour, Shahriar; Keyhanmanesh, Rana
Abstract : This study aimed to evaluate the effect of prolonged dietary nitrate supplementation on diabetic reproductive system. Abstract : The aim of this study was to evaluate the effect of prolonged dietary nitrate supplementation on the gonadotropin level, testicular histology and morphometry, expression of miR-34b and p53 mRNA, and spermatogenesis in streptozotocin-induced diabetic male rats. Methods : Fifty male Wistar rats were divided into 5 groups: Control (C), control + nitrate (CN), diabetes (D), diabetes + insulin (DI), and diabetes + nitrate (DN). Diabetes was induced using 45 mg kg −1 of streptozotocin intraperitoneally. Rats in the CN and DN groups were administered sodium nitrate in drinking water (100 mg L −1 ). NPH insulin (2–4 U d −1 ) was injected subcutaneously in the DI group for 2 months. Nitrate and insulin supplementation was started one month after confirmation of diabetes. Results : Nitrate supplementation in the DN group significantly increased the body weight ( p < 0.05), sperm parameters ( p < 0.001), indices of spermatogenesis ( p < 0.001), and testis histopathology as well as decreased the blood glucose level ( p < 0.001) compared to the untreated diabetic group, although it had no significant effect on testicular parameters, LH and FSH levels. Nitrate administration in the DN group also decreased miR-34b ( p < 0.001) and p53 mRNA ( p < 0.001) expression, and increased serum insulin and NOx levels compared to the untreated diabetic rats. Conclusions : Chronic nitrate supplementation in streptozotocin-induced diabetic rats improved fertility parameters, which may be associated with increased miR-34b and decreased p53 mRNA.